EXPERIMENTAL STUDY OF FLEXURAL STRENGTH (OUT OF PLANE) ON WALL PANEL BY USING AUTOCLAVED AERATED CONCRETE AND BAMBOO REINFORCEMENT - Miftakhul Jannah; Sri Murni Dewi; Hendro Suseno (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2021)
The use of wall panels in the construction sector is tremendously familiar, because the implementation process is faster and more efficient. However, concrete wall panels are considered quite heavy, so that in this research will be discussed to learn more about wall panels by utilizing AAC lightweight bricks and bamboo reinforcement to reduce the panel's own weight without reducing its structural strength. In this present study, the specimen was made with a scale model to be tested for flexural capacity when receiving out of plane loads. Based on the research results, there were differences in the characteristics between AAC panels and ordinary reinforced concrete panels so that the flexural strength test with out of plane loading, AAC panels have increased flexural capacity more than ordinary reinforced concrete panels.